Degradation of reserve starch from the seed of wild and domesticated Phaseolus vulgaris L. - Vargas-Vázquez, Ma. L. Patricia; Uscanga-Mortera, Ebandro; Padilla-Chacón, Daniel; Vibrans Lindemann, Heike; Yáñez-Jiménez, Petra; García-Esteva, Antonio (Revista Mexicana de Ciencias Agrícolas, 2025)
Domestication has modified the size and type of seed reserves; this raises the question of whether these modifications have had an impact on metabolism and the mobilization of these reserves during germination and seedling establishment. The research aimed to determine the effect of domestication on cotyledons, embryonal axis and dark-grown seedlings of domesticated and wild beans. In 2019, eight seeds of three improved varieties and three wild collections were germinated at 25 °C, another eight seeds with exposed radicles were sown in grow bags and the seedlings obtained were kept for 14 days in darkness. The germinated seeds and seedlings were dissected into their structures and their dry mass and the concentrations of starch, glucose, fructose and sucrose were determined; likewise, the number of cells and the number of starch granules mm-2 and their dimensions were also determined in cotyledons. The design used was completely randomized with four replications. On average, the improved varieties had 11 and three times more dry matter in cotyledons and embryonal axis compared to wild varieties, and seven, nine and 13 times more dry matter in root, shoot and remnant of cotyledons, respectively. Concentrations of starch, glucose, and sucrose per gram of dry mass were higher in cotyledons from improved varieties; in contrast, concentrations of starch, glucose, and fructose were higher in the embryonal axis of the wild ones. In the root, wild varieties had higher concentrations of starch, fructose, and sucrose, and in the shoot, domesticated ones had more glucose, fructose, and sucrose. Wild varieties had 42% more cells and 30% more starch granules than domesticated ones per unit area. Domestication modifies the composition and mobilization of reserves during germination and seedling establishment.
Keywords: beans; germination; reducing sugars; reserve substance